The flight home effect: Evidence from the syndicated loan market during financial crises - Giannetti, Mariassunta; Laeven, Luc (Journal of Financial Economics, 2012)
This paper shows that the collapse of the global market for syndicated loans during financial crises can in part be explained by a flight home effect whereby lenders rebalance their loan portfolios in favor of domestic borrowers. The home bias of lenders' loan origination increases by approximately 20% if the bank's home country experiences a banking crisis. This flight home effect is distinct from flight to quality because borrowers of different quality are equally affected. The results indicate that the home bias in capital allocation tends to increase when adverse economic shocks reduce the wealth of international investors.